Penal conciliation as an alternative to recovery of smuggled proceeds of crime - Khechana, Lazhar; Berni, Karima (Journal of Human Sciences, 2023)
The process of recovering the proceeds of corruption offences abroad is considered the most important manifestation of the fight against corruption because of its legal, political and social importance, but the experience to prove that it remains. A complex and ineffective path. Therefore, the tools of traditional criminal justice have not led to this end, hence the interest of adopting another approach that is based on the mechanisms that provide justice, Restorative, notably through the criminal reconciliation that is deemed to be a Rapid justice, The Court of Justice of the European Communities.